Mechanical properties of magnesium alloys for medical application: A review. (November 2018) - Chen, Junxiu; Tan, Lili; Yu, Xiaoming; Etim, Iniobong P.; Ibrahim, Muhammad; Yang, Ke
Abstract: Magnesium alloys as a class of biodegradable metals have great potential to be used as implant materials, which attract much attention. In this review, the mechanical properties of magnesium alloys for medical applications are summarized. The methods to improve the mechanical properties of biodegradable magnesium alloys and the mechanical behaviors of Mg alloys in biomedical application are illustrated. Finally the challenges and future development of biodegradable magnesium alloys are presented.